2022
DOI: 10.3390/ijerph19116876
|View full text |Cite
|
Sign up to set email alerts
|

Sun Protection and Tanning Behaviors in Caregivers: Prevalence, Determinants, and Associations with Children’s Behaviors

Abstract: The association between skin cancer and ultraviolet radiation (UVR) is well established, and sun protection behavior represents an important preventative measure. In children, caregivers play a key role in this regard. The subject of this study was threefold: whether caregivers of 1 to 11 year-old children are more likely to use sun protection measures compared to non-caregivers, whether considering oneself a role model is associated with sun protection behaviors, and whether their sun protection and risk beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Most parents in Germany used sunscreen in the beach setting (82%), while they used sunscreen to a lesser extent in the outdoor garden setting ( Gefeller et al, 2016 ). Caregivers’ attitude was positively associated with children's behaviour; parents who considered themselves role models were five times more likely to use sunscreen on the face (OR = 5.08, p < 0.001) ( Diehl et al, 2022 ). Further, it has been reported that parents applied sunscreen and other sun-protective measures in younger children more often; likewise, adolescent boys have less sun-protective behaviour than girls ( Karlijn Thoonen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most parents in Germany used sunscreen in the beach setting (82%), while they used sunscreen to a lesser extent in the outdoor garden setting ( Gefeller et al, 2016 ). Caregivers’ attitude was positively associated with children's behaviour; parents who considered themselves role models were five times more likely to use sunscreen on the face (OR = 5.08, p < 0.001) ( Diehl et al, 2022 ). Further, it has been reported that parents applied sunscreen and other sun-protective measures in younger children more often; likewise, adolescent boys have less sun-protective behaviour than girls ( Karlijn Thoonen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous surveys have found that despite public health campaigns to promote sun-protection behaviour, many parents do not often adhere to sun safety recommendations and that the use of sunscreen by children is still suboptimal. 7,12,15,16 In Europe, 29%-60% of children report having experienced sunburn at least once during the previous year.…”
Section: E Duc At Ion a Bou T Photoprotec Tion I N E A R Ly L Ifementioning
confidence: 99%
“…This will largely depend on parents' and other caregivers' understanding about photoprotection and their ability to implement appropriate sun‐protection behaviour in the children in their care. However, numerous surveys have found that despite public health campaigns to promote sun‐protection behaviour, many parents do not often adhere to sun safety recommendations and that the use of sunscreen by children is still suboptimal 7,12,15,16 . In Europe, 29%–60% of children report having experienced sunburn at least once during the previous year.…”
Section: Education About Photoprotection In Early Lifementioning
confidence: 99%
“…A sample size of 4000 was determined by a sample size calculation using the analysis PROC POWER SAS software (SAS Institute Inc.). Participants were selected using a two-stage random sampling procedure (Diehl et al 2022). All participants gave informed verbal consent prior to the interviews.…”
Section: Sample and Data Collectionmentioning
confidence: 99%